Event monitoring of parallel computations - Gruzlikov, Alexander M.; Kolesov, Nikolai V.; Tolmacheva, Marina V. (Zielona Góra: Uniwersytet Zielonogórski)
The paper considers the monitoring of parallel computations for detection of abnormal events. It is assumed that computations are organized according to an event model, and monitoring is based on specific test sequences.
Keywords: parallel computations; monitoring; discrete event systems; real time systems